2021
DOI: 10.2147/ott.s312162
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Self-Expandable Metallic Stent Combined with Double 125I Seeds Strands or Single 125I Seeds Strand in the Treatment of Advanced Perihilar Cholangiocarcinoma with Malignant Obstructive Jaundice

Abstract: The purpose of this study was to compare the safety and effectiveness of a selfexpandable metallic stent (SEMs) with a novel brachytherapy biliary drainage catheter (BBDC, double 125 I seeds strands) or a single 125 I seeds strand in the treatment of advanced perihilar cholangiocarcinoma (pCCA) with malignant obstructive jaundice (MOJ). Methods: From September 2016 to December 2018, we retrospectively enrolled patients with biliary stent implantation after receiving either BBDC loaded with 125 I seeds (doubles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…The results of our multivariate analysis showed that functionally success drainage and antitumor treatment were independent factors of better survival and improved patient outcomes in these patients with advanced tumors. The median OS in this study was 135 days, which was slightly greater than the intervals of 79–104 days reported in previous studies [ 16 , [18] , [19] , [20] ]. What is important is that the median survival time of 8.4 months in the patients with functionally successful drainage was significantly greater than in the non-functionally successful group (3.2 months).…”
Section: Discussioncontrasting
confidence: 68%
“…The results of our multivariate analysis showed that functionally success drainage and antitumor treatment were independent factors of better survival and improved patient outcomes in these patients with advanced tumors. The median OS in this study was 135 days, which was slightly greater than the intervals of 79–104 days reported in previous studies [ 16 , [18] , [19] , [20] ]. What is important is that the median survival time of 8.4 months in the patients with functionally successful drainage was significantly greater than in the non-functionally successful group (3.2 months).…”
Section: Discussioncontrasting
confidence: 68%
“…Technical success was classified as satisfactory placement of the stent through the stricture with the seed strand or seeds in the appropriate position and brisk flow of contrast through the stent into the intestine. Clinical success was defined as the serum total bilirubin level dropped by 75% of the preoperative value within 4 weeks [ 15 ]. The duration of stent patency was defined as the interval between stent deployment and stent restenosis.…”
Section: Methodsmentioning
confidence: 99%
“…[52][53][54] ILBT, using 192 Ir or 125 I seed strands, can be used with SEMSs to improve their patency rates and present a viable option for the management of patients with MOJ. 55,56 Interventional Technique for ILBT Treatment of Bile Duct Cancers Brachytherapy in patients with biliary tract cancers is delivered through a percutaneous transhepatic biliary drainage (PTBD) catheter, placed under fluoroscopic guidance, or through catheters placed in the tumor bed during surgery. The percutaneous transhepatic or transduodenal techniques can be used for biliary drainage and device catheter placement.…”
Section: Intraluminal Brachytherapymentioning
confidence: 99%
“…52 53 54 ILBT, using 192 Ir or 125 I seed strands, can be used with SEMSs to improve their patency rates and present a viable option for the management of patients with MOJ. 55 56…”
Section: Intraluminal Brachytherapymentioning
confidence: 99%